2023
DOI: 10.1111/acps.13534
|View full text |Cite
|
Sign up to set email alerts
|

Delirium‐related psychiatric and neurocognitive impairment and the association with post‐intensive care syndrome—A narrative review

Abstract: Introduction Delirium is common among patients admitted to the intensive care unit (ICU) and its impact on the neurocognitive and psychiatric state of survivors is of great interest. These new‐onset or worsening conditions, together with physical alterations, are called post‐intensive care syndrome (PICS). Our aim is to update on the latest screening and follow‐up options for psychological and cognitive sequelae of PICS. Method This narrative review discusses the occurrence of delirium in ICU settings and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 130 publications
(322 reference statements)
0
8
0
Order By: Relevance
“…Longer-term monitoring is indicated given that symptoms of PTSD can be both delayed (36) and persistent (37) and that qualitative research has shown that it takes time for a family fully to appreciate how they have been impacted by this experience (38). Follow-up services are developing in adult settings with a number now beginning to suggest algorithms for how to target “at risk” cases for early screening (24) and using novel strategies such as multidisciplinary rehabilitation prescriptions (23). Guidance has also been made available on how to build a business case for the addition of mental health provision to multidisciplinary ICU teams (39) which could be adapted for use in pediatric settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer-term monitoring is indicated given that symptoms of PTSD can be both delayed (36) and persistent (37) and that qualitative research has shown that it takes time for a family fully to appreciate how they have been impacted by this experience (38). Follow-up services are developing in adult settings with a number now beginning to suggest algorithms for how to target “at risk” cases for early screening (24) and using novel strategies such as multidisciplinary rehabilitation prescriptions (23). Guidance has also been made available on how to build a business case for the addition of mental health provision to multidisciplinary ICU teams (39) which could be adapted for use in pediatric settings.…”
Section: Discussionmentioning
confidence: 99%
“…In the world of adult intensive care, consensus is building on ways to measure outcomes and develop models of working that assess and address cognitive and emotional impairment post-discharge (22)(23)(24). After treatment on PICU parents also report significant levels of emotional/behavioral problems in their children in follow-up studies (25) and when consulted about research priorities, rate the importance of research highly (26).…”
Section: At the Bedsidementioning
confidence: 99%
“…care patients has led to the development of post-intensive care syndrome and difficulty returning to the original level of pre-ICU function among the survivors [15]. PICS is multifactorial and multifaceted, consisting of physical impairments, cognitive deficits, and mental health problems in ICU survivors and their families [9,11,[16][17][18][19]. Complications are more common in septic ICU patients and endure for years post-ICU.…”
Section: Journal Of Anesthesia and Intensive Care Medicinementioning
confidence: 99%
“…Finally, cognitive impairment is observed in approximately 40% of patients suffering from PICS [11,9,[16][17][18][19]. It presents as reduced memory, poor executive function, weakened language, inattention, and progressive dementia [16].…”
Section: Journal Of Anesthesia and Intensive Care Medicinementioning
confidence: 99%
“…In addition to the impact of delirium on patients while in hospital, its adverse long‐term consequences are increasingly recognised, particularly after admissions to intensive care units. Ramnarain et al 9 review the relatively new concept of a post‐intensive care syndrome, defined as new or worsened impairments in physical, cognitive or mental health after critical illness and persisting beyond acute care hospitalisation 10 . Such problems occur in about half of intensive care unit survivors, and the authors argue that early detection using a structured follow‐up is essential for initiating treatment and enhancing the quality of life.…”
mentioning
confidence: 99%